Platelet-Derived Microvesicles in Cardiovascular Diseases - Zaldivia, Maria T. K.; McFadyen, James D.; Lim, Bock; Wang, Xiaowei; Peter, Karlheinz (Frontiers in Cardiovascular Medicine, 2017)
Microvesicles (MVs) circulating in the blood are small vesicles (100–1,000 nm in diameter) derived from membrane blebs of cells such as activated platelets, endothelial cells, and leukocytes. A growing body of evidence now supports the concept that platelet-derived microvesicles (PMVs), the most abundant MVs in the circulation, are important regulators of hemostasis, inflammation, and angiogenesis. Compared with healthy individuals, a large increase of circulating PMVs has been observed, particularly in patients with cardiovascular diseases. As observed in MVs from other parent cells, PMVs exert their biological effects in multiple ways, such as triggering various intercellular signaling cascades and by participating in transcellular communication by the transfer of their “cargo” of cytoplasmic components and surface receptors to other cell types. This review describes our current understanding of the potential role of PMVs in mediating hemostasis, inflammation, and angiogenesis and their consequences on the pathogenesis of cardiovascular diseases, such as atherosclerosis, myocardial infarction, and venous thrombosis. Furthermore, new developments of the therapeutic potential of PMVs for the treatment of cardiovascular diseases will be discussed.